2018
DOI: 10.12691/ajphr-6-1-2
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health Facility-based Delivery and Child Mortality in Nigeria: Insights from 2013 Nigeria Demographic and Health Survey

Abstract: Background: Health facility-based delivery has been considered to be an important factor in reducing maternal and child deaths. Evidence suggests that 63 per cent of women aged 15-49 years deliver at home. This study seeks to examine the effect of health facility-based delivery on child mortality in Nigeria. Methods: Secondary data from the 2013 Nigeria Demographic and Health Survey was used. Variables on place of delivery as well as demographic and socio-economic characteristics of the study sample were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
0
1
Order By: Relevance
“…Women who were divorced/ separated experienced higher childhood mortality than the nevermarried. This finding contradicts that of Adedini (2013) but is consistent with Aregbeshola and Khan (2018) and Akinyemi et al (2017) that found being married is protective of child mortality. The authors argued that being unmarried could jeopardise a child's health because it can rob a child of adequate fatherly care.…”
Section: Discussioncontrasting
confidence: 50%
“…Women who were divorced/ separated experienced higher childhood mortality than the nevermarried. This finding contradicts that of Adedini (2013) but is consistent with Aregbeshola and Khan (2018) and Akinyemi et al (2017) that found being married is protective of child mortality. The authors argued that being unmarried could jeopardise a child's health because it can rob a child of adequate fatherly care.…”
Section: Discussioncontrasting
confidence: 50%
“…La littérature scientifique abonde en travaux empiriques sur la mortalité des enfants dans les pays en développement. Ils portent en majorité sur les tendances et les inégalités sociales de cette mortalité (Ngatchou, 1990 ;Akoto, 1993 ;Adeolu et al, 2016 ;Maïga, 2016 ;Adewusi et al, 2018 ;Antai, 2011 ;Akinyemi et al, 2017 ;Garenne 2010 ;Boco, 2011 ;Brockerhoff et Hewett, 2000 ;Keats et al, 2018). Grâce aux données des enquêtes démographiques et de santé (EDS), on sait que la mortalité des enfants en Afrique subsaharienne, comme partout ailleurs, est fortement liée à l'éducation des mères (ou des couples) et à leur niveau de vie.…”
Section: Introductionunclassified
“…On sait aussi que les enfants vivant en milieu rural ont une mortalité généralement plus forte que ceux vivant en milieu urbain. Ces trois variables d'identification sociale (éducation, niveau de vie, milieu de résidence) sont des déterminants couramment pris en compte dans les analyses différentielles de la mortalité des enfants (Baya, 1998 ;Ngatchou, 1990 ;Akoto, 1993 ;Adeolu et al, 2016 ;Maïga, 2016 ;Adewusi et al, 2018) en raison de leurs fortes relations avec cette dernière, au niveau tant individuel qu'agrégé. Plusieurs autres inégalités de mortalité sont souvent évoquées : le sexe (Tabutin et al, 2001, cité par Tabutin et Schoumaker, 2004, le rang de naissance (Bocquier, 1991), la religion (Brockerhoff et Hewett, 2000 ;Modiano et al, 1999), l'ethnie (Victoria et al, 2020Brockerhoff et Hewett, 2000), l'occupation des parents Duflo, 2012 ;Adeolu et al, 2016) et le statut matrimonial de la mère (Soura, 2009).…”
Section: Introductionunclassified